PENERAPAN BUDAYA KERJA PROFESIONAL DI BADAN KESATUAN BANGSA DAN POLITIK PROVINSI RIAU - Ningsih, Yuliana; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study describes how the application of professional work culture in Badan Kesatuan Bangsa and Politik province Riau.It aims to determine the extent of the work culture of employees and analyze in factors that affect the application of professional work culture.Professional work culture that is applied not yet fully realized well.This is caused by the constraints of each individual employed to have an attitude, ethics, and discipline in working different and also the level adherence to the leadership and loyalty in a work that is still lacking. Research application of professional work culture in Badan Kesatuan Bangsa and Politik province Riau using a theoretical concept Paramitha in Ndraha (2002:80) work culture is divided in to: 1) attitudes toward work, 2) behavior at work. This study uses qualitative research methods with an assessment of descriptive. In data collection researchers use interviewing techniques, observation, and documentation by using key informants as a source triangulation techniques in testing the validity of the information. These result indicate that the application of professional work culture in Badan Kesatuan bangsa dan Politik provinsi riau. Not optimal or not completely be implemented by employees at work. There are obstacles in the implementation of professional work culture of employees this is because each individual employee can not change their ways of thinking about the importance a good working culture for smooth implementation of the tasks in the work. Lack of leadership role in overseeing and controlling employee directly in work.the leader in creating a harmonious atmosphere among fellow employees work without deferent for each member or subordinate lead. Key Words : Work culture, discipline, leadership